Multibody Energy States With exact electron-electron interactions - Goodman, James W (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In a class on quantum mechanics in 1964 at LSU a question was asked whether the potential energies of a multibody could be added up to give the energy state. It was stated that Vanagas was somewhat successful in using 2 body states. In 1971 two hypotheses were made using current Hilbert Space applied to the multibody Schrdingers Equation and the wave functions derived. The ground states of atoms with atomic number Z=2-20 were calculated and agreed with Hartree-Fox iterations. The success was due to the exact electron-electron interactions.